Inter-regional multilateralism in the Global South: the zone of peace and cooperation in the South Atlantic - Abdenur, A. E.; Mattheis, F.; Seabra, P. (Inter-organizational Relations in International Security: cooperation and competition, 2018)
Do inter-regional organizations in the Global South possess particular characteristics and dynamics? In this chapter, we investigate the Zone of Peace and Cooperation in the South Atlantic (ZOPACAS), an initiative originally launched in 1986 through the United Nations General Assembly (UNGA). This trans-regional initiative was created exclusively by (and for) developing countries. Rather than being inter-regional in the sense of an interaction between two regional organizations, ZOPACAS transcends two established regions and incorporates the Atlantic shores of both South America and Africa, as well as the maritime space between them.